Efficacy of Chinese Herbal Injections for the Treatment of Primary Nephrotic Syndrome: A Bayesian Network Meta-Analysis of Randomized Controlled Trials - Yu, Hangxing; Han, Miaoru; Lin, Wei; Wang, Lin; Liu, Panying; Yang, Kang; Pei, Ming; Yang, Hongtao (Frontiers in Pharmacology, 2020)
objectivew:we performed a network meta-analysis to investigate the efficacy of CHIs in the treatment of PNS. Methods: A systematic literature review including studies published from the establishment of each database to May 28, 2020, was conducted in PubMed, the Cochrane Library, Embase, Web of Science, CBM,CNKI,VIP and WF.Two evaluators independently screened the literature, extracted data and the Cochrane Reviewer's Handbook 5.1 method was used to evaluate the quality of included studies. The differences in efficacy of different CHIs were compared and ranked using Stata 16.0 software. Surface under the cumulative ranking curve (SUCRA) probability values were applied to rank the examined treatments. Clustering analysis was performed to compare the effects of CHIs between two different outcomes. Results: A total of 41 eligible randomized controlled trials involving 2879 patients and nine CHIs were included. Nine CHIs were Xiangdan injection (XDI), Huangqi injection (HQI), Shenkang injection (SKI), Danshen injection (DSI), Yinxingdamo injection (YXI), Dengzhanhuasu injection (DZI), Danhong injection (DHI), Shuxuetong injection (SXI), Chuanxiongqin injection (CXI). The results of the network meta-analysis showed that: with Western medical (WM) treatment as a co-intervention, in terms of improving the total clinical effectiveness and serum albumin level, DHI was the most likely to be the best choice for treatment (SUCRA=82.2%); YXI had the highest probability of being the best option in terms of reducing 24-hour urinary protein excretion (SUCRA= 97.8%); in cholesterol-lowering comparisons, the SUCRA value allows for the most likely to be the best treatment is DZI (SUCRA=84.5%). SXI was the most effective CHIs in terms of lowering triglycerides (SUCRA=85.6%), whereas on the reducing fibrinogen, the efficacy of CXI was significant (SUCRA=67.6%). The result cluster analysis indicated that YXI and DHI were the best interventions with respect to total clinical effectiveness, 24-hour urinary protein excretion and serum albumin. Conclusions: CHIs were found to be superior to WM alone in the treatment of PNS and may be beneficial for patients with PNS. WM+YXI and WM+DHI had the potential to be the best CHI with respect to the total clinical effectiveness, 24-hour urinary protein excretion and serum albumin. However, more well-designed randomized controlled trials are still warranted.